"It makes almost no difference which algorithm you use": on the modularity of predictive policing - Lally, Nick (Urban geography, 2022)
Predictive policing is built on a simple assumption: crime exhibits predictable patterns, which means future crime risk can be forecast using historic crime data. While critics have raised concerns over the use of biased data in these systems, less is known about how software is actually used within infrastructures of governance. Drawing on interviews with software developers and an analysis of technical, promotional, and academic materials, I show how internal and external pressures separate predictive policing from the concrete practices it attempts to transform. I argue that predictive policing is a modular technology, plugged into the black box of policing. This modularity separates software developers from the practices they attempt to transform, while enabling them to deflect criticism away from the programs they build. Modularity also means that software can be reconfigured and connected to other systems, which threatens to undermine the set of best practices that guide its development.